Developing the Country Brand of Taiwan from the Perspective of Exports - Chen , Chun-An; Lee , Shang-Ru (Asian Journal of Empirical Research, 2013)
People are familiar with the concept of product branding, but the concept of nation branding has just emerged in recent years. It is a significant forward-thinking trend. The related researches about nation branding are relatively few. The scopes include exports, governance, culture, people, tourism, immigration and investment. Taiwan is an island country that is lacking in natural resources, so international trade is very important. The purpose of this study is to explore the suitable export products to develop Taiwan's brand as a nation. This study is analyzed using a two-stage method. The first stage uses the Fuzzy Delphi method to screen items. Then we used the Fuzzy AHP method to evaluate the weights of items. The results showed that the important items are "IC design", "smart phone", and "nanotechnology products". The Taiwan government can make the development strategy about nation branding based on these products.